A new family of fourth-order methods for multiple roots of nonlinear equations - Liu, Baoqing; Zhou, Xiaojian (Nonlinear Analysis: Modelling and Control, 2013)
Recently, some optimal fourth-order iterative methods for multiple roots of nonlinear equations are presented when the multiplicity m of the root is known. Different from these optimal iterative methods known already, this paper presents a new family of iterative methods using the modified Newton’s method as its first step. The new family, requiring one evaluation of the function and two evaluations of its first derivative, is of optimal order. Numerical examples are given to suggest that the new family can be competitive with other fourth-order methods and the modified Newton’s method for multiple roots.
Keywords: nonlinear equations; iterative method; multiple roots; the modified Newton’s method; optimal order